The politics of an 'incomplete' Banking Union and its 'asymmetric' effects. Issue 8 (17th November 2019) - Quaglia, Lucia
ABSTRACT: What explains the establishment of an 'incomplete' Banking Union and its 'asymmetric' effects? This paper takes an intergovernmentalistapproach to explain the incompleteness of Banking Union as well as its asymmetric functioning. The institutional design of Banking Union was a compromise between the preferences of the main member states, albeit it was closer to the positions of Germany. In turn, the incomplete institutional design of Banking Union has affected its subsequent functioning. It has produced asymmetric effects that have mostly penalised the member states in the Southern periphery of the euro area, notably, Italy, Spain, Portugal and Greece, which, to no avail, have called for completion of Banking Union. Banking Union has not severed the doom-loop in these countries and has weakened the institutional capacity of the national authorities to deal with ailing banks in these countries, without sufficiently strengthening the capacity of supranational authorities to do so.